Enhancing Competence in Battery-Based Electric Vehicle Installation and Programming at SMK Negeri Jambu (Lembaga Pengembangan Kinerja Dosen, 2025)
This community service program was implemented to overcome the limited technical capacity of teachers and students at SMK Negeri Jambu in mastering the installation and programming of battery-based electric vehicles, which is a crucial skill in preparing competent human resources for the rapidly evolving green vehicle industry. The program specifically aimed to enhance participants’ knowledge and skills in several key areas, including the installation of electric motor control systems, management of battery energy, and maintenance of essential electric vehicle components. To achieve these goals, the activities were carried out using a blended method that integrated lectures, demonstrations, and direct hands-on practice, supported by continuous mentoring and systematic evaluation. In addition, QR Code–based learning resources were incorporated to provide participants with quick and efficient access to digital instructional materials, allowing for more flexible and independent learning. The evaluation results revealed significant progress in both the theoretical understanding and practical abilities of the participants. They were able to demonstrate improvements not only in operating and maintaining electric vehicle systems but also in identifying problems and performing troubleshooting independently. These findings suggest that the program effectively contributed to building sustainable competencies for teachers and students, equipping them with relevant skills aligned with the needs of the green automotive industry, while also promoting technological adaptation and innovation in vocational education.